Comminuted medial malleolar fractures – a series of 5 cases - Air Machado da Silva , Bruno; de Souza Pereira, Paulo Victor; Friaça Tatibana, Murilo; Pinheiro Lima, Daniel; Coelho Thomé, Andre Luiz (Journal of the Foot & Ankle, 2022)
Objective: To demonstrate fixation options for comminuted fractures of the medial malleolus. Methods: We retrospectively analyzed patients operated on for ankle fractures who had comminuted fractures of the medial malleolus between 2014 and 2018. Five patients were included in the study, 3 women and 2 men aged 19 to 37 years. Four cases were fixed with a tension-band wiring technique using Kirschner wires and cerclage, and 1 case with lag screws and buttress plate. Results: Four cases progressed satisfactorily (AOFAS >70), and 1 case progressed to ankle arthrodesis. Conclusion: Fixation with a tension-band wiring technique using Kirschner wires and cerclage may be an alternative to osteosynthesis in comminuted fractures of the medial malleolus with small fragments. Fixation with lag screws and buttress plate may be used in cases with larger fragments. Level of Evidence IV; Therapeutic Studies; Cases Series.